Are climate change adaptation strategies interrelated? Evidence from Borana pastoral communities, southern Ethiopia - Feyissa, Abraham Abera; Angassa, Ayana; Tadesse, Menfese (Frontiers in Climate, 2025)
Climate change manifests itself in recurrent droughts and erratic rainfall, resulting in diminished local water and animal feed resources. This has led to the death of large numbers of livestock, which are the basis of pastoral livelihoods in the Borana Zone, southern Ethiopia. In response to climate change impacts, the Borana pastoral community adopted various adaptation strategies to sustain their livelihoods. The present study examined the factors that determine pastoralists’ adaptation strategies and the intensities of their adoption and identified barriers to their implementation. A multivariate probit (MVP) and an ordered probit model were employed to analyze the adoption decisions of 240 households and a problem confrontation index to identify barriers to the adoption of adaptation strategies. The results indicate that while there are various adaptation strategies, some have a very low adoption rate. The majority of households (90%) used at least two of these adaptation strategies, and only 1.67% used all of them. Most importantly, the majority of adaptation strategies were interdependent, which indicates that some strategies are complementary and others are substitutable. Promoting complementary strategies within a package may help boost adaptation strategies and enhance resilience to the impacts of climate change through their synergies. Education, the dependence ratio, farming activity, access to extension services, and market distance significantly affect adoption decisions and adoption intensity. Similarly, bush encroachment, regionalization policies, improper settlement patterns, and farmland expansion hinder the implementation of adaptations. Hence, interventions that facilitate the adoption of climate change adaptation strategies and address barriers to their implementation can improve pastoral and agro-pastoral resilience to climate change. It would also be crucial to develop land-use planning that encourages the coexistence of livestock grazing and crop cultivation in order to maintain ecological balance and minimize conflict.